DERIVATIONAL SUFFIXES FORMING NOUN IN “ENIGMA” BOOK BY AMANDA MARGARETH - Alifia Hanifah; Mu'man Mu'man (PROJECT (Professional Journal of English Education), 2023)
Derivational suffix is a process of adding a suffix to the base of a word to compose a new word and a new meaning of the word, this process also changes the word class. There are four kinds of suffixes: nominal suffixes, verbal suffixes, adjectival suffixes, and adverbial suffixes. This research aims to analyze derivational suffixes forming nouns and identifying kinds of suffixes forming nouns in a book. The researcher used qualitative as the method and qualitative descriptive as the design in analyzing derivational suffixes forming nouns, the theory used to analyze the data was the theory proposed by Carstairs-Mccarthy (2002). The data source of this research was taken from the “Enigma” book by Amanda Margareth, while the data collection technique used documentation by reading the book, writing words containing noun suffixes, grouping words containing noun suffixes into various kinds of noun-forming suffixes, and making conclusion. The result showed 41 data found in the book. There were two kinds of suffixes forming nouns found in the book. The first was suffixes forming a noun from a verb consists of 21 data or 51,2%. From the 21 data, 8 derivational processes were found after adding suffixes forming nouns from verbs. The suffixes found were –ion (6), –tion (2), –ation (4), –ment (2), –ing (1), –ure (3), –ence (1), and –er (2). The second was suffixes forming a noun from an adjective consists of 20 data or 48,8%. From the 20 data, 7 derivational processes were found after adding suffixes forming nouns from an adjective. The suffixes found were –ce (7), –ity (6), –ness (3), –er (1), –dom (1), –ion (1) and –th (1). Keywords:  Derivational Suffixes; Nominal Suffixes; Book